Case Report: Venous pulsatile tinnitus induced by enlarged oblique occipital sinus and resultant diverticulum/dehiscence of the sigmoid-jugular wall - Hsieh, Yue-Lin; Wang, Shenjiang; Wang, Wuqing (Frontiers in Surgery, 2023)
Pulsatile tinnitus (PT) caused by enlarged oblique occipital sinus (OOS) and resultant diverticulum/dehiscence of the sigmoid-jugular wall has not been described in previous literature. This study recruits one case of PT induced by ipsilateral enlarged OOS and sigmoid-jugular wall diverticulum (case 1) alongside one case of PT induced by ipsilateral enlarged OOS and sigmoid-jugular wall dehiscence (case 2). Various radiologic and computational techniques including computed tomography (CT), magnetic resonance (MR) imaging, Doppler ultrasound, and computational fluid dynamics (CFD) simulation were implemented. Transmastoid sinus wall reconstruction was performed on case 1 with a large sigmoid-jugular diverticulum potentially traumatizing the facial nerve canal. Contrast-enhanced CT or MR venogram images coupling with three-dimensional reconstructed are advantageous in revealing the covert route of OOS that runs under the cerebellum and drains directly into jugular bulb (JB) region. PT in case 1 was successfully eliminated after transmastoid sinus wall reconstruction surgery. Tinnitus handicap inventory score in case 1 reduced from 70 to 0. The ipsilateral jugular outflow mean velocity (Vmn) and flow volume (FVOL) were 42.5 cm/s and 25.9 g/s (case 1 prior to surgery) and 56.6 cm/s and 41.2 g/s (case 2), respectively. Based on CFD simulation, the peak flow velocity in OOS was 1.85 m/s and 2.1 m/s, the wall pressure of the diverticular dome and dehiscence area of the SS-JB wall was 1724.7 Pa and 369.8 Pa in case 1 and 2, respectively. Enlarged OOS caries greater flow kinetic energy that possibly induces sigmoid-jugular wall diverticulum/dehiscence; transmastoid surgical method is safe and therapeutically effective against PT induced by enlarged OOS.